Structure-activity relationship and interaction mechanism of nine structurally similar flavonoids and α-amylase. (November 2021) - Zhao, Yiling; Wang, Ming; Huang, Ganhui
Graphical abstract: Highlights: Hydroxylation and methoxylation of flavonoids greatly influence the inhibition on PPA. The structure of Luteolin exhibits potent inhibitory effect. Hydrophobic interaction and hydrogen bonds are essential for the interaction. Flavonoids could alter the secondary structure of PPA. Abstract: In this study, the structure-activity relationship and interaction mechanism of nine flavonoids and porcine pancreatic α-amylase were studied through enzyme kinetics, multispectral analysis and molecular simulation. The analysis of the structure-activity relationship illustrated that hydroxylation at C4′ and C5′ position of flavonoids increased the inhibitory activity against α-amylase while the methylation at the corresponding position decreased it. According to the fluorescence quenching assay, all flavonoids could efficiently quench the intrinsic fluorescence of amylase by static mechanism and the thermodynamic parameters of representative Luteolin and Quercetin indicated the key role of hydrogen bonds and van der Waals interactions. The multispectral study suggested that the binding of flavonoids alters the secondary structure of α-amylase, leading to significant inhibition. Moreover, these findings were further confirmed by molecular docking which demonstrating the importance of hydrogen bonding and hydrophobic forces in flavonoid and porcine pancreatic α-amylase interactions.